Tiempo, legado y promesas: coloquio intergeneracional en torno a las bodas de diamante de la Revista de Neuro-Psiquiatría - Alarcón, Renato D.; Querol, Mariano; Mori, Grover; Jerí, F. Raúl; Ponce, Manuel; Sarabia, Silvana; Custodio, Nilton; Guillén, Daniel; Vega-Dienstmaier, Johann; Cruzado, Lizardo (Revista de Neuro-Psiquiatría, 2015)
.